Miller Fisher syndrome with sinus arrest - Nobuko Shiraiwa; Mitsumasa Umesawa; Sachiko Hoshino; Tsuyoshi Enomoto; Susumu Kusunoki; Akira Tamaoka; Norio Ohkoshi (MDPI AG, 2017)
Dysautonomia in Guillain-Barre syndrome (GBS) rarely causes serious cardiovascular complications, such as sinus arrest. Miller Fisher syndrome (MFS) is recognized as a variant of GBS. There have been few reports regarding the association between MFS and dysautonomia. We describe a case of a 68-year-old man with ophthalmoplegia, bulbar palsy, truncal ataxia, and areflexia. He was diagnosed with MFS because he exhibited the classical clinical triad and had elevated serum anti- GQ1b immunoglobulin G levels. A magnetic resonance imaging scan of his head was normal. His 24-hour Holter recording showed sinus arrest. He was treated with intravenous immunoglobulin, whereupon his symptoms gradually improved. This included the sinus arrest, which was considered a symptom of dysautonomia in MFS. Therefore, clinicians should be mindful of dysautonomia not only in GBS patients, but also in cases of MFS.